Epidemiology of Helicobacter pylori infection in the Czech Republic - Bureš, Jan; Kopáčová, Marcela; Koupilová, Ilona; Voříšek, Viktor; Rejchrt, Stanislav; Beránek, Martin; Seifert, Bohumil; Pozler, Oldřich; Živný, Pavel; Douda, Tomáš; Pintérová Kolesárová, Martina; Pintér, Michal; et al. (Helicobacter, 2006)
BACKGROUND: Prevalence of Helicobacter pylori infection has been estimated to range from 60 to 95% in the former communist countries of Central and Eastern Europe. The aim of this study was to evaluate H. pylori infection prevalence in a representative sample of the Czech population. The second objective was to describe difference of H. pylori prevalence between different social groups of children and adults. MATERIALS AND METHODS: A total of 2509 persons aged 5-100 years, randomly selected out of 30,012 persons of the general population, took part in the study. H. pylori infection was investigated by means of 13C-urea breath test. Breath samples were analyzed by isotope ratio mass spectrometry. Social and demographic characteristics were based on data from self-completed questionnaires. RESULTS: Using the total Czech population as a standard, we estimated the age-standardized prevalence of H. pylori in males aged 5+ years at 41.9% (95% CI 39.0%, 44.8%) and in females aged 5+ years at 41.4% (95% CI 38.6%, 44.3%) in 2001. Prevalence of H. pylori increased with age but was not related to gender. Children of mothers with basic or lower education, living in crowded accommodations, without access to running warm water, and residing in smaller towns appear to be at the highest risk. Low education and heavy smoking are most strongly associated with prevalence of H. pylori positivity in adults and adolescents. CONCLUSIONS: This is a unique study based on a representative sample of the general population in a Central European country. The overall prevalence of H. pylori is lower than previously assumed and could partly reflect a substantial recent decrease in H. pylori prevalence in the Czech Republic. Consistent with earlier studies, H. pylori infection is strongly influenced by socioeconomic conditions and childhood poverty.
Keywords: Female; antibakteriální látky; lidé středního věku; dechové testy; Cross-Sectional Studies; Adolescent; mužské pohlaví; Financing, Organized; senioři nad 80 let; Humans; dospělí; stupeň vzdělání; Anti-Bacterial Agents; průřezové studie; Helicobacter Infections; Czech Republic; lidé; Educational Status; Middle Aged; Aged, 80 and over; senioři; společenská třída; ženské pohlaví; Child; Česká republika; Aged; financování organizované; Breath Tests; infekce vyvolané Helicobacter pylori; Social Class; dítě; Adult; Male; mladiství